Effects of Educational Program Based on Self-Esteem Enhancement on Weight Status in Obese Women - Mohammad A. Seifrabiei; Mohammad Ahmadpanah; Mohammad Kazemzadeh; Sanaz Ebrahimi (Wolters Kluwer Medknow Publications, 2024)
Background: Most obese people do not have high self-esteem. This study was conducted to evaluate the effect of self-esteem education on the weight status of obese women. Methods: This Randomized Clinical Trial (RCT) was performed on 46 obese women (BMI >30) in Hamadan during 2021-2022. By simple convenient sampling and block randomization, the samples were divided into two equal groups. In both groups, routine lifestyle and diet recommendations were prescribed. In the intervention group, eight sessions of self-esteem training were performed specifically. In two groups BMI was measured and the Cooper-Smith Self-Esteem Inventory (CSEI) was filled out before and after the intervention. SPSS 20 was used to analyze the data. Statistical significance was considered at p < 0.05. Results: The mean age of the participants in the intervention and control groups was 27.95 (5.02) and 30.25 (5.46) years respectively (t38 = 1.39, p = 0.17). BMI was comparable in two groups before the study (32.47 vs. 33.13 in the intervention and control group respectively, (t38 = 1.02, p = 0.31), but decreased significantly in the intervention group at the end (30.38 vs. 32.90, t38 = 3.76, p = 0.001). The mean self-esteem scores of the two groups were similar at the beginning (27.10 vs. 27.60 in the intervention and control group respectively, (t38 = 0.52, p = 0.60) but increased significantly in the intervention group at the end (30.10 vs. 27.35, t38 = 2.99, p < 0.001). Conclusions: The findings suggest that self-esteem educational programs can increase the self-esteem score and decrease BMI in obese women and should be considered as a treatment modality in these women.